Return to sport and patient satisfaction after arthroscopic Bankart repair: a single-institution experience - Yeow Boon Tan; Ken Lee Puah; Roland Weng Wah Chong; Kee Leong Ong; Yi-Jia Lim; Dave Yee Han Lee (Singapore Medical Journal)
Introduction: Arthroscopic Bankart repair is a widely accepted procedure to treat recurrent shoulder dislocation. This study aims to describe our experience with arthroscopic Bankart repair and its functional outcome. Methods: 107 patients who underwent arthroscopic Bankart repair from 2008 to 2013 were followed up for a minimum of three years and reviewed by an independent observer. 80 consented to being interviewed using the Oxford Shoulder Instability Score (OSIS) and Simple Shoulder Test. Results: 82 shoulders (two bilateral) were studied. Mean age at first dislocation was 19.4 ± 3.4 (12.0–31.0) years. Mean follow-up was 4.4 ± 1.3 (3.0–9.0) years and 2.5 ± 3.0 (0.1–15.4) years elapsed from first dislocation to surgery. 41 (50.0%) patients played overhead or contact sports and 44 (53.7%) played competitive sports before injury; 8 (9.8%) patients reported recurrence of dislocation, which was significantly associated with playing competitive sports before injury (p <0.039), 5 (6.1%) underwent revision surgery and 22 (26.8%) reported residual instability after surgery. 49 (59.8%) patients returned to playing sports, 75 (91.5%) were satisfied with their surgery and 79 (96.3%) were willing to undergo the surgery again. 74 (90.2%) patients had two-year good/excellent OSIS, which was significantly associated with playing competitive sports before injury (p = 0.039), self-reported stability after surgery (p = 0.017), satisfaction with surgery (p = 0.018) and willingness to undergo surgery again (p = 0.024). Conclusion: Arthroscopic Bankart repair yields good functional outcomes and is associated with high patient satisfaction, although not all patients return to sports.